A Miniaturized Low-Weight 2.4 GHz Circularly Polarized Antenna Using 3D Printing Technology - Xinyue Guo; Qian Chen; Xiangyu Zhou; Minjia Chai; Zhixiang Huang; Lixia Yang; Yingsong Li (IEEE Access)
3D printing technology is applied to the processing and manufacturing of antennas because it can improve the freedom of antenna design and fabricate antennas that are difficult to achieve with conventional processes. In this paper, a compact bamboo dragonfly-liked circularly polarized antenna is designed using 3D printing technology. The antenna consists of two pairs of orthogonally distributed S-shaped radiation arms. Two ring-delay lines connect two pairs of S-shaped arms to introduce two 90° phase delays to achieve circular polarization. A $50~Ω $ coaxial cable connected the radiation arms to feed the antenna. Simulation results show that a bandwidth of 2.33-2.65 GHz with S $11\lt -10$ dB and a bandwidth of 2.33-2.46 GHz with axial ratio (AR) <3 dB are obtained. A sample with an overall Size of 41 mm $× 41$ mm $× 5.5$ mm ( $0.33λ _{0} × 0.33λ _{0} × 0.044λ _{0}$ , $f_{0} =2.4$ GHz) was fabricated to verify the design. The measured working bandwidth is 2.3-2.6 GHz with S $11\lt -10$ dB. The measured realized gain and radiation efficiency are 1.36 dBic and 80.35% at 2.4 GHz, respectively. This proposed antenna with a lightweight of 1.7 g can maintain a stable landing from the air, which can be deployed from air vehicles and to build an outdoor sensor network.